Comprehensive evaluation of long-term trends in occupational exposure: Part 1. Description of the database. Issue 5 (May 1998) - Symanski, E; Kupper, L L; Rappaport, S M
Abstract : OBJECTIVES: To conduct a comprehensive evaluation of long term changes in occupational exposure among a broad cross section of industries worldwide. METHODS: A review of the scientific literature identified studies that reported historical changes in exposure. About 700 sets of data from 119 published and several unpublished sources were compiled. Data were published over a 30 year period in 25 journals that spanned a range of disciplines. For each data set, the average exposure level was compiled for each period and details on the contaminant, the industry and location, changes in the threshold limit value (TLV), as well as the type of sampling method were recorded. Spearman rank correlation coefficients were used to identify monotonic changes in exposure over time and simple linear regression analyses were used to characterise trends in exposure. RESULTS: About 78% of the natural log transformed data showed linear trends towards lower exposure levels whereas 22% indicated increasing trends. (The Spearman rank correlation analyses produced a similar breakdown between exposures monotonically increasing or decreasing over time.) Although the rates of reduction for the data showing downward trends ranged from -1% to -62% per year, most exposures declined at rates between -4% and -14% per year (the interquartile range), with a median value of -8% per year. Exposures seemed to increase at rates that were slightly lower than those of exposures which have declined over time. Data sets that showed downward (versus upward) trends were influenced by several factors including type and carcinogenicity of the contaminant, type of monitoring, historical changes in the threshold limit values (TLVs), and period of sampling. CONCLUSIONS: This review supports the notion that occupational exposures are generally lower today than they were years or decades ago. However, such trends seem to have been affected by factors related to the contaminant, as well as to the period and type of sampling.